Using corpus analysis to extend experimental research: Genre effects in L2 writing. (August 2021) - Lee, Jongbong
Abstract: This study investigates differences in the writing performance of L1-Korean learners of English as a foreign language (EFL) in response to tasks requiring different genres of writing. Utilizing data controlled for L1 and proficiency level from the Gachon Learner Corpus, the study partially replicates a study by Yoon and Polio (2017), and examines genre effects by comparing descriptive and argumentative essays. A total of 481 essays (270 descriptive and 211 argumentative) from two proficiency groups were analyzed in order to evaluate the effects of different genres on EFL learners' writing performance. Using syntactic complexity and lexical complexity measures, the analysis found statistically significant differences between the two genres. The L2 learners produced more subordination, more of particular structures, and more sophisticated vocabulary in argumentative writing than in descriptive writing. These findings of genre effects can be interpreted on the basis of either the cognition hypothesis or the role of genres' communicative function. No proficiency differences were detected between the two genres except in lexical diversity. The study's findings suggest that existing corpora may be useful for studies seeking to confirm or extend experimental research.